Multiple HPV infections among men who have sex with men engaged in anal cancer screening in Abuja, Nigeria - Nowak, Rebecca G.; Schumaker, Lisa M.; Ambulos, Nicholas P.; Ndembi, Nicaise; Dauda, Wuese; Nnaji, Chinedu H.; Mitchell, Andrew; Mathias, Trevor J.; Jibrin, Paul; Darragh, Teresa M.; Olaomi, Oluwole; Crowell, Trevor A.; et al. (My University, 2020)
Background: Anal precancers and cancers can be detected during screening with high-resolution anoscopy (HRA). The sensitivity of HRA depends on the burden and duration of human papillomavirus (HPV) among those screened as well as anoscopist proficiency, which is highly correlated with prior screening experience. Our objective was to compare the identification and type of HPV and the likelihood of HRA-detected precancer for men who have sex with men (MSM) undergoing their first HRA-screening in Nigeria. Methods: MSM were recruited from an HIV test-and-treat cohort, TRUST/RV368, into a new anal cancer screening program. Anal swabs obtained during screening underwent Ion Torrent next-generation sequencing using barcoded HPV PCR broad-spectrum primers 5+/6+ to detect up to 161 HPVs. All high-risk (HR) HPVs and the most abundant low-risk (LR)-HPVs were evaluated as type-specific infections with some categorized as belonging to a multiple infection. HRA screening results included benign, low-grade squamous intraepithelial lesions (LSIL), or HSIL as detected by cytology or histology. Multivariable logistic regression was used to assess the association of HPV and other cofactors with any SIL. Results: Among 342 MSM, 60% were HIV-infected, 89% were under 35 years of age, and 51% had 8 or more years since anal coital debut. Of those with SIL, 89% had LSIL and only 11% had HSIL. Prevalence of any HPV and high-risk (HR)-HPV was 92% and 74%, respectively. The most prevalent genotypes in rank order were HPV6 (31%), HPV16 (23%), HPV42 (20%), HPV11 (18%), HPV45 (18%), and HPV51 (17%). For multiple HR-HPVs, 31% had a single HR-HPV, 32% had 2-3, and 10% had 4 or more. Low-risk HPVs, type 6 and/or 11, were common (42%) and were significantly associated with SIL (adjusted odds ratio [aOR]:1.8, 95% confidence interval [CI]: 1.1–3.1) together with perianal warts (aOR:6.7, 95% CI: 3.3–13.5). In contrast, HR-HPV and multiple HR-HPVs were not significantly associated with SIL (all p > 0.05). Conclusions: Detection of HSIL was low. Although HR-HPV was abundant, HSIL development also depends on the duration of HR-HPV infections and the anoscopist's level of experience. As our cohort ages and the anoscopist becomes more skilled, detection of HSIL will likely improve.
Keywords: AIDS; Gesundheit; Medizin; 610; Nigeria; Krebs